Mint Leaves (Mentha piperita) as Herbal Dietary Supplement: Effect on Performance and Economics of Broiler Chicken Production - Khurshid, Asra; Banday, M.T.; Adil, S.; Untoo, Madeeha; Afzal, Insha (Pakistan Journal of Nutrition, 2016)
A study was conducted to evaluate the effect of dietary supplementation of Mint leaves (Mentha piperita) with or without enzyme treatment on performance and economics of broiler chicken production. To achieve the envisaged objectives, a feeding trail was conducted with 225 day old commercial broiler chicks. The chicks were procured from a reputed source and reared together until 7 days of age. On 8th day, the chicks were individually weighed, distributed randomly into 5 treatment groups of 3 replicates with 15 chicks each. Birds in the control group (T1) were fed diets without additives, whereas in T2 and T3 basal diet was supplemented with raw mint leaves @ 1% (T2) and 2% (T3). In T4 and T5, enzyme treated mint leaves @ 1 and 2% were added to the basal diet, respectively. The body weight, feed consumption and feed conversion ratio were recorded at weekly intervals and economics of feeding was worked out at the end of trial. The results revealed that the birds fed diets supplemented with either raw and enzyme treated mint leaves attained significantly (p<0.05) higher live body weight when compared with the control group. A significantly (p<0.05) highest improvement in the body weight was observed in T5 when compared with the other groups. No significant (p>0.05) difference in the cumulative feed consumption was observed among various treatment groups. The cumulative feed conversion ratio showed a significant (p<0.05) improvement in all the treatment groups when compared with the control. A reduction in feed cost/kg live weight gain was observed in the birds fed 1% enzyme treated mint leaves (T4) in the diet. In conclusion, 1% enzyme treated mint leaves were found to be effective in economizing the broiler production.